Comparing detection rates of near-infrared transpalpebral transillumination, ultrasonography and radiography for foreign bodies in the anterior segment of the eye (Ukrainian Journal of Ophthalmology, 2025)
Background: Penetrating globe injury is a leading cause of registered visual disability among working-age adults. Despite advances in imaging techniques, the detection of an intraocular foreign body (IOFB) in the projection of the ciliary body is still a challenge for the ophthalmologist.Purpose: To compare detection rates of near-infrared transpalpebral transillumination, ultrasonography and radiography for foreign bodies situated in the anterior segment of the eye.Material and Methods: Thirty male patients (30 eyes; age, 21 to 65 years) with penetrating globe injuries and suspected foreign body in the anterior segment of the eye (the anterior chamber, lens, anterior vitreous cavity) were under our observation. The fellow eye was unaffected. Patients underwent visual acuity assessment, biomicroscopy, ophthalmoscopy, ultrasound scanning of the anterior and posterior segment of the eye, ultrasound biometry, radiography and near-infrared transpalpebral transillumination (NIR TPT).Results: The use of a non-invasive NIR TPT method in conjunction with traditional imaging modalities (radiography and ultrasound) resulted in a ten percent increase in the rate of detection of anterior segment foreign bodies due to the detection of some X-ray-negative IOFBs and identification of small (less than 1 mm) IOFBs.Conclusion: The NIR TPT method allows for non-invasive visualization of anterior segment foreign bodies of various compositions in patients with penetrating globe injuries. The use of a non-invasive NIR TPT method in conjunction with traditional imaging modalities resulted in a ten percent increase in the rate of detection of foreign bodies due to the detection of some X-ray-negative IOFBs and identification of small (less than 1 mm) IOFBs. Massive subconjunctival hemorrhages hamper adequate detection of foreign bodies in the projection of the ciliary body by NIR TPT due to intensive absorption of near-infrared light.
Keywords: penetrating globe injury; intraocular foreign body; infrared radiation; transillumination